PENGARUH GAYA BAHASA GENERASI Z DALAM BERBAHASA INDONESIA DI ERA GLOBALISASI TERHADAP KEUTUHAN BAHASA INDONESIA - Rufaida, Bilqis Syifa (Translation and Linguistics (Transling), 2023)
The influence of Generation Z's language style in speaking Indonesian in the era of globalization has a significant impact on the integrity of Indonesian as the national language and national cultural identity. Generation Z, who grew up in an environment filled with information technology and global media, displays a relaxed, fast, and creative style of communication, using abbreviations, emoticons, foreign words, and informal language styles. The influence of globalization and the popularity of English have also led to shifts in communication preferences, where Indonesian may become less attractive to Generation Z. Through a literature review, data searches were conducted to identify the language style of Generation Z and analyze it to find out the impact of using that style of language. The search results show the impact of Generation Z's style on the integrity of the Indonesian language in this globalization era.